Methadone as a “Tumor Theralgesic” against Cancer - Michalska, Marta; Katzenwadel, Arndt; Wolf, Philipp (Frontiers in Pharmacology, 2017)
Methadone has beneficial characteristics as an analgesic against cancer pain, including high bioavailability, multiple receptor affinities, and lack of active metabolites that might induce adverse side effects. However, methadone has an own pharmacological profile that should be considered in the treatment of cancer patients. There is evidence from preclinical studies that methadone could also elicit antitumor activity by downregulating the threshold of apoptosis and to enhance the effects of different chemotherapeutic agents. This confirms the concept to use methadone also as a chemosensitizer in the future treatment cancer. Our article discusses major issues about the role of methadone as a possible “tumor theralgesic”, combining tumor therapeutic and analgesic activities.